If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = -41 Reorder the terms: -8 + 3x = -41 Solving -8 + 3x = -41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 3x = -41 + 8 Combine like terms: -8 + 8 = 0 0 + 3x = -41 + 8 3x = -41 + 8 Combine like terms: -41 + 8 = -33 3x = -33 Divide each side by '3'. x = -11 Simplifying x = -11
| 3.65=x-1.4 | | 7(z-2)-3z=44 | | x-8=0.64 | | -5+2x=13 | | 7x+4=10y-7 | | 100+1x=5x-1x | | -6x^2-35x-33=0 | | 50=8+2a | | -26=5y-6 | | 6x^2+35x+33=0 | | 8x+47=8[x+5] | | 12x-18=15x | | 6x^2-35x-33=0 | | 100+1x=5x-1 | | -3i/7=-7/8 | | (5y^3-2y^2)(-35y+14)=0 | | 2(5x+7)=24 | | 6f+10=2f-30 | | 18-7f=-9 | | 10x+600=664 | | 7x/8=-10 | | 14b=16b+8 | | X-(-16)=16 | | (8X-5)-(3X-3)=0 | | 48=16s | | -5x-9=-24 | | 1=w-4 | | 6c+4=c+24 | | -5l/9=25 | | 5x+7=-33 | | x^4-6x^2-2=0 | | 45+1.99m=68.88 |